International recruitment of mental health nurses to the national health service: a challenge for the UK - Peter Phiri; Sana Sajid; Ardic Baykoca; Suchith Shetty; Daisy Mudoni; Shanaya Rathod; Gayathri Delanerolle (BMC Nursing, 2022)
Abstract The UK’s National Health Service (NHS) has been dealing with a shortage in the nursing workforce for the past few decades. With the ongoing COVID-19 pandemic and post-Brexit effects, it is important now more than ever to concentrate on recruiting new staff and retaining current staff in the National Health Service. The increasing demand for mental health services stresses the importance of prioritising recruitment of mental health nurses. One of the main strategies being implemented to combat this shortage is the recruitment of internationally trained mental health nurses. Whilst this is a favourable solution, the multiple challenges this proposal brings makes it hard for the National Health Service to practically implement this to increase staff numbers. In this discursive position paper, we consider the difficulties the National Health Service is currently facing in terms of recruiting mental health nurses and then discuss the importance of and need for international recruitment including the strategies that are currently being implemented. The challenges and obstacles associated with this proposed resolution will also be addressed.